Experimental study on shear strength and deterioration behavior of silty clay under dry-wet-freeze-thaw cycles - Haotian Guo; Yinglian Sun; Chao Sun; Hongyan Gu (Scientific Reports)
Abstract To investigate the influence of dry-wet, freeze-thaw, and their coupled cyclic effects on shear strength and deterioration behavior of silty clay, direct shear tests were performed on silty clay with different initial moisture content under the above cyclic conditions. A shear strength deterioration model of silty clay was established based on the indoor test data by using the Logistic function to predict shear strength parameters under dry-wet, freeze-thaw, and dry-wet-freeze-thaw cycles. Results are below. Under dry-wet, freeze-thaw, and their coupled cycles, shear stress-displacement curves can be classified into strain-softening and strain-hardening types. Increasing the moisture content, decreasing the vertical stress, and increasing the cycle times of the three cycles mentioned above all promote the transition of the curve from strain-hardening to strain-softening. As dry-wet, freeze-thaw, and their coupled cycles increase, the cohesion and internal friction angle deteriorate rapidly in the early stage and slowly in the later stage. The maximum degree of deterioration of shear strength parameters decreases as the moisture content increases during dry-wet cycles and dry-wet-freeze-thaw cycles, while it increases during freeze-thaw cycles, with the highest during dry-wet-freeze-thaw cycles. The research findings can predict and evaluate the shear performance of silty clay in seasonal frozen soil regions.